Pemanfaatan Obat Herbal Antidiabetes Hasil Riset untuk Suplementasi Pengobatan Penderita Diabetes Melitus yang Rentan Covid-19 di Kelompok Lansia Posyandu Mawar, Kecamatan Baki Sukoharjo - Muhtadi; EM Sutrisna; Susila, Ihwan; Andi, Andi Suhendi (Universitas Muhammadiyah Surakarta, 2023)
The elderly and diabetes mellitus are a groups that is vulnerable to exposure to Covid-19 infection. Therefore, they must keep their blood sugar levels under control and their immune conditions. Posyandu lansia mawar is a forum for the elderly to share and check their health, with more than 50 members. This community service activity (PkM) aims to apply antidiabetic herbal medicinal products from research that are efficacious and safe. The implementation uses a Participatory Action Research (PAR) approach, namely the active involvement of posyandu participants to utilize antidiabetic herbal medicinal products for supplementation of diabetes mellitus (DM) treatment and care, health promotion, and health checks in the form of measuring blood pressure and blood sugar levels. This activity is a collaboration of researchers, students, business (CV. Arba'in, product provider), and the community. The results of this activity showed that the elderly after consuming antidiabetic herbal medicines combined with other herbal packages felt an improvement in their complaints and their blood sugar levels in general tended to decrease. The elderly after education understands about diabetes and how to control their blood sugar levels. In addition, they also understand how to use natural and easy-to-find ingredients to maintain health, especially controlling blood sugar levels.